PENINGKATAN KETERAMPILAN PERANCANGAN DAN PEMBUATAN WASTAFEL MINIMALIS ERGONOMIS UNTUK SISWA SEKOLAH MENENGAH KEJURUAN NEGERI (SMKN) 7 TANGERANG BANTEN - I Wayan Sukania; Cindy P; Agni P (PROSIDING SERINA, 2021)
One of the activities that must be done in the context of preventing Covid is washing hands. Washing hands for at least 20 seconds using soap in running water is effective in killing germs and bacteria, including the corona virus. Efforts to break the chain of virus spread were also carried out at SMKN 7 Tangerang, Banten. One of the facilities provided is a sink. However, the available sinks are inadequate both in terms of condition and quantity. Therefore, it is very necessary to make an ergonomic minimalist sink to complement the school as well as practice making it to improve student skills. PKM activities are carried out at SMKN 7 Tangerang, which is located in Dasana Indah Housing Karawaci Tangerang. PKM activities are carried out in 2 stages, namely debriefing and practice. The practical activity resulted in 3 units of ergonomic minimalist sinks. Questionnaires were given at the beginning and end of the activity to determine the amount of addition to the knowledge, skills and insights of the participants. In general, there was an increase in the knowledge, insight and skills of the trainees.